Pengaruh Jenis Warna Umbi Ubi Jalar (Ipomea Batatas L.) Dan Lama Pengukusan Terhadap Karakteristik Kimia Dan Fisik Mie Kering - Maria Goreti Wahyuni (Fakultas Pertanian, 2022)
Dry noodles are dried food products made from wheat flour with the addition of other foods and food additives which are allowed to be in the form of typical noodles. The high increase in consumption and demand for noodles will simultaneously increase the volume of wheat imports. Excessive consumption of wheat flour will have an allergic effect for celiac sufferers. Sweet potato pasta as a local food can be used to reduce on imported flour and provide health effects as an antioxidant for people with diabetes mellitus. The difference in sweet potato color can affect the physicochemical and functional characteristics of sweet potatoes. In the steaming process, starch gelatinization and gluten coagulation occur so that the occurrence of dehydration of water from gluten will cause noodle elasticity. Steaming needs to be considered to form a cohesive and fairly elastic dough period.